2000
DOI: 10.1007/pl00001057
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modelling of a Landslide-generated Tsunami: The 1979 Nice Event

Abstract: On the 16th of October 1979, a part of the Nice new harbour extension, close to the Nice international airport (French Riviera), slumped into the Mediterranean Sea during landfilling operations. A submarine slide with initial volume close to seashore of about 10 millions m 3 , which could have evolved later into an avalanche, was followed by a small tsunami, noticed by several witnesses in the ''Baie des Anges.'' The maximum tsunami effects were observed 10 km from the slide location near Antibes city, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
105
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(109 citation statements)
references
References 11 publications
4
105
0
Order By: Relevance
“…When compared to the volume of slumps that have generated tsunami elsewhere, such as a 13 000 m 3 slump that generated a 0.4 m high tsunami in Monterey Bay (USA) in 1989 (Ma et al, 1991), then it is conceivable that a submarine slump in the Dover Straits approaching the proportions to that of the Beachy Head failure may generate locally a significantly higher tsunami. Also, slumping can initiate close to the coast, as Assier-Rzadkiewicz et al (2000) examine the case of artificial landfill that slumped into the Mediterranean during the construction of Nice Airport in southern France (16 October 1979) that generated tsunami locally over 3 m high inundating the nearby city of Antibes. However, tsunami attenuated rapidly away from the slump area due to strong wave dispersion so, as with some other landslidegenerated tsunami, the effect was restricted locally.…”
Section: Possibility Of Submarine Slidesmentioning
confidence: 99%
“…When compared to the volume of slumps that have generated tsunami elsewhere, such as a 13 000 m 3 slump that generated a 0.4 m high tsunami in Monterey Bay (USA) in 1989 (Ma et al, 1991), then it is conceivable that a submarine slump in the Dover Straits approaching the proportions to that of the Beachy Head failure may generate locally a significantly higher tsunami. Also, slumping can initiate close to the coast, as Assier-Rzadkiewicz et al (2000) examine the case of artificial landfill that slumped into the Mediterranean during the construction of Nice Airport in southern France (16 October 1979) that generated tsunami locally over 3 m high inundating the nearby city of Antibes. However, tsunami attenuated rapidly away from the slump area due to strong wave dispersion so, as with some other landslidegenerated tsunami, the effect was restricted locally.…”
Section: Possibility Of Submarine Slidesmentioning
confidence: 99%
“…Many studies have suggested possible factors that can trigger submarine landslides, e.g., earthquakes, hurricanes or cyclic loading, oversteepening of slopes, overpressure, gas hydrate dissociation, sea-level change, and volcanic activity (Prior and Coleman 1982;Weaver and Kuijpers 1983;Moore et al 1989;Assier-Rzadkiewicz et al 2000;Sultan et al 2004a, b;Fine et al 2005). However, it is still a question why submarine landslides can occur on slopes as low as 1° and travel a long distance over such mild slopes.…”
Section: Introductionmentioning
confidence: 99%
“…Subaerial slides displace a considerable volume of water at relatively high speed as they slide into the water from the slope. One of the well known examples of subaerial landslides is the event in Nice on 16 October 1979, when a volume of ground slumped into the Mediterranean Sea during landfilling operations (Assier-Rzadkiewicz, 2000). Other examples are the landslide of 3 November 1994 in Skagway (Kulikov et al, 1996) during the collapse of a cruise ship wharf undergoing construction, and the underwater landslide of 17 July 1998 in Papua New Guinea caused by a moderate earthquake (Tappin et al, 1999).…”
Section: Introductionmentioning
confidence: 99%